A filosofia da alteridade ou o problema da ausência na filosofia contemporânea - Rocha, Talita Carolina Romualdo (2014)
The present dissertation launches a philosophical overview that includes the alterity in the thought of Friedrich Nietzsche. Dwelling in analyzing the main Nietzschean themes as \"will,\" \"beyond-the-man\" and \"death of God\" scrolls through a path that points to his philosophy as a participant in a perspective of alterity. In this sense, the conceptual work of Nietzsche is seen here as a glimpse into an ethic that right necessarily implies acceptance of the other, the different. It is from here that will target, thinking this ethics, the philosophy of Emmanuel Levinas, which raises questions about alterity, proposing an interpersonal relationship, i.e, a face-to-face relationship. Similarly, the present work focuses on Jacques Derrida, in order to present us with a new ethic, deconstructing the Levinasian thought, stressing in the differánce a shift from I (self) to difference, thinking in the other. Returning to Nietzsche, the dissertation shows that your thinking is shrouded in the shadows, because there are numerous questions about human behavior, it is referred to Levinasian philosophy with regard to the concepts of Il ya and Hypostasis, comprising a transition to the awakening of Shadows Light, the ascent of man, not rising for a metaphysics, but, rather, to earthly experiences. The research presented and completed in this dissertation makes us understand that the major concern of these thinkers is to think about a way of being in the world, observing the changes we suffer throughout our existence, and to seek, in the words of Nietzsche, a philosophy before of the noon.